Local Knowledge and its Applicability in Secondary Level Classroom Instructions - Bhattarai, Taranath (Curriculum Development Journal, 2023)
This study aims at identifying the applicability of local knowledge in school level classroom instructions and analyzing task-based approaches, methods and techniques in classroom practices for the development of skill-based education in study areas. It also attempts to recommend some strategies for the application of local knowledge in classroom instructions for the development of practical education through functional or task-based classroom instructions. Based on the qualitative method, the data have been collected through observation and semi-structured interviews. The collected data have been analyzed by carrying out immersion, understanding, abstraction, synthesis, illumination of phenomena and integration and critique of findings. The key findings of the study showed plenty of diverse local knowledge available in study areas and proved to be very useful in carrying out teaching learning activities in the classroom by applying various instructional techniques and curricular implementations in the secondary level.